1979
DOI: 10.1073/pnas.76.12.6201
|View full text |Cite
|
Sign up to set email alerts
|

Removal of an adenine-like molecule during activation of dinitrogenase reductase from Rhodospirillum rubrum.

Abstract: During the activation of the inactive dinitro- Dinitrogenase reductase (Rr2) from Rhodospirillum rubrum is inactive as isolated (1) and has been shown to have two pentose, two phosphate, and two adenine-like molecules (Ad) attached per 60,000 molecular weight dimer (2). The role of these groups in activation is discussed in this paper.Other enzymes have been shown to have ribose, phosphate, and adenine covalently attached. The first of these was glutamine synthetase (GS) from Escherichia coli; it has up to 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 14 publications
3
37
0
Order By: Relevance
“…Under activating assay conditions, which did not affect the activity significantly when cells had not been exposed to ammonium, the inhibition resulting from exposure of the culture to ammonium could be substantially eliminated in vitro by adding Mn2' and Mg2+ in concentrations known to be required for DRAG activity in an in vitro assay with purified proteins (41,42,51,59). These results are consistent with the in vivo ADP-ribosylation of wild-type component II in response to ammonium and the in vitro reactivation of this protein by DRAG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under activating assay conditions, which did not affect the activity significantly when cells had not been exposed to ammonium, the inhibition resulting from exposure of the culture to ammonium could be substantially eliminated in vitro by adding Mn2' and Mg2+ in concentrations known to be required for DRAG activity in an in vitro assay with purified proteins (41,42,51,59). These results are consistent with the in vivo ADP-ribosylation of wild-type component II in response to ammonium and the in vitro reactivation of this protein by DRAG.…”
Section: Methodsmentioning
confidence: 99%
“…This mixture (pH 7.8) consisted of 100 mM MOPS, 12.5 mM ATP, 80 mM creatine phosphate, 12.5 U of creatine phosphokinase, and 25 mM Na2S204 and contained different MgCl2 and MnCl2 concentrations: 10 mM MgCl2 for nonactivating conditions, in which DRAG is known to be inactive, and 25 mM MgCl2 and 0.5 mM MnCl2 for activating conditions, in which DRAG is capable of activating modified component II (41,42).…”
Section: Methodsmentioning
confidence: 99%
“…Ludden & Burris (1978) have reported that inactive nitrogenase from Rhodospirillum rubrum contains phosphate, ribose and adenine-like molecules attached to the Fe-protein of nitrogenase. It has also been found that a Mn2 +-dependent enzyme (Nordlund & Eriksson, 1979;Ludden & Burris, 1979), recently purified from Rhodospirillum rubrum (Gotto & Yoch, 1982), removes the adenine moiety from the Fe-protein of nitrogenase (Ludden & Burris, 1979), producing the 'switch on' effect.…”
Section: Introductionmentioning
confidence: 99%
“…The inactive enzyme can be activated in vitro by the addition of an activating enzyme isolated from the chromatophore membrane fraction (8,9). This activation results from the removal of at least part of the modifying group (6, [8][9][10][11][12]. The modifying group may also be removed in vitro by mild heat treatment, resulting in activation of the enzyme (13).…”
mentioning
confidence: 99%